Adiponectin offers protection against L166P mutant DJ-1-induced neuronal cytotoxicity mediated by APPL1-dependent AMPK activation. (1st May 2014) - Li, Xuemei; Geng, Jianhong; Liu, Junling
Abstract : Parkinson's disease (PD) is the second most common neurodegenerative disease in the world. L166P mutant DJ-1 has been linked with a genetic form of the disease. Preventing neurotoxicity of DJ-1 familial mutations has become a new therapeutic target for PD. Adiponectin, the most abundantly secreted adipokine, has displayed its protective roles in pathologies of various types of diseases. In this study, we investigate whether adiponectin is protective against neurotoxicity induced by familial L166P mutant DJ-1 in PD. Our results demonstrate that adiponectin treatment could attenuate increased levels of reactive oxygen species and nitric oxide induced by the DJ-1L166P mutation. In addition, adiponectin could rescue impaired mitochondrial membrane potential induced by DJ-1L166P . Importantly, we verified that both adiponectin receptors, type 1 (AdipoR1) and type 2 (AdipoR2), are expressed in human neuroblastoma M17 cells. Our results also demonstrate that the protective effects of adiponectin against DJ-1L166P -induced neuronal cytotoxicity under 1-methyl-4-phenylpyridinium ion (MPP+) treatment require binding of adiponectin to its cell surface receptors. Finally, we found that the protective effects of adiponectin against DJ-1L166P depend on AMP-activated protein kinase (AMPK) activation mediated by the endosomal adaptor protein, APPL1 (adaptor protein with phosphotyrosine binding, pleckstrin homology domains and leucine zipper motif). These data suggest that adiponectin may have potential for implementation in novel therapies against PD.